Understanding GaN/InGaN core–shell growth towards high quality factor whispering gallery modes from non-polar InGaN quantum wells on GaN rods. (6th November 2017) - Tessarek, C; Rechberger, S; Dieker, C; Heilmann, M; Spiecker, E; Christiansen, S
Abstract: GaN microrods are used as a basis for subsequent InGaN quantum well (QW) and quantum dot deposition by metal-organic vapor phase epitaxy. The coverage of the shell along the sidewall of rods is dependent on the rod growth time and a complete coverage is obtained for shorter rod growth times. Transmission electron microscopy measurements are performed to reveal the structural properties of the InGaN layer on the sidewall facet and on the top facet. The presence of layers in the microrod and on the microrod surface will be discussed with respect to GaN and InGaN growth. A detailed model will be presented explaining the formation of multiple SiN layers and the partial and full coverage of the shell around the core. Cathodoluminescence measurements are performed to analyze the InGaN emission properties along the microrod and to study the microresonator properties of such hexagonal core–shell structures. High quality factor whispering gallery modes with Q ∼ 1200 are reported for the first time in a GaN microrod/InGaN non-polar QW core–shell geometry. The GaN/InGaN core–shell microrods are expected to be promising building blocks for low-threshold laser diodes and ultra-sensitive optical sensors.